Legal Analysis of Auction on Negligence of Home Ownership Credit Customers Wahbah Az-Zuhaili's Perspective at BTN Syariah Medan - Sary Mahvira; Tetty Marlina Tarigan (UNIVERSITAS PAKUAN, 2023)
The procedure for pasting auction marks should go through court procedures and has the legal force of remaining in the decision. Unfortunately, this did not happen in the act of negligence of home ownership loans organized by BTN Syari'ah. Every customer who starts acting in bad faith, BTN Syariah Medan starts putting the sticker on the customer's home who starts to be uncooperative. The act was considered to be beyond the limit according to Wahbah Az Zuhaili because it had passed the rules of the auction procedure. This journal is compiled using empirical legal research methods. The results of the study showed that BTN Syariah Medan was considered unprocedural in carrying out auction procedures and BTN Syariah was considered to exceed the limit in collection efforts according to Wahbah Az Zuhaili